Short comments on an energy pumping levels in a MEMS Gyroscope vibrating problem, by using of an global and local optimal linear control design - Chavarette, Fábio Roberto (2010)
This paper deals with an energy pumping that occurs in a (MEMS) Gyroscope nonlinear dynamical system, modeled with a proof mass constrained to move in a plane with two resonant modes, which are nominally orthogonal. The two modes are ideally coupled only by the rotation of the gyro about the plane's normal vector. We also developed a linear optimal control design for reducing the oscillatory movement of the nonlinear systems to a stable point. Copyright © 2009 by ASME.